2013
DOI: 10.1093/cje/bet075
|View full text |Cite
|
Sign up to set email alerts
|

Does high public debt consistently stifle economic growth? A critique of Reinhart and Rogoff

Abstract: We replicate Rogoff (2010a and2010b) and find that coding errors, selective exclusion of available data, and unconventional weighting of summary statistics lead to serious errors that inaccurately represent the relationship between public debt and GDP growth among 20 advanced economies in the post-war period. Our finding is that when properly calculated, the average real GDP growth rate for countries carrying a public-debt-to-GDP ratio of over 90 percent is actually 2.2 percent, not −0.1 percent as published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
507
5
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(558 citation statements)
references
References 3 publications
9
507
5
17
Order By: Relevance
“…The second part addresses the issue of reverse causality, and considers how that might itself vary between countries. In both cases, we used Reinhart and Rogoff's data, made available by Herndon et al (2013).…”
Section: Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…The second part addresses the issue of reverse causality, and considers how that might itself vary between countries. In both cases, we used Reinhart and Rogoff's data, made available by Herndon et al (2013).…”
Section: Methodsologymentioning
confidence: 99%
“…The second set of comments was initiated in spring 2013 with the publication of a working paper from the Political Economy Research Institute at the University of MassachusettsAmherst (Herndon, et al, 2013). As a graduate student, Herndon undertook an assignment to repeat the analyses of a key paper -in his case Reinhart and Rogoff's -and found that he could not replicate their findings with the dataset used in the publications referred to above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While their analysis has been heavily criticized, e.g. by Herndon et al (2014), their findings nonetheless sparked an intense debate about the growth effects of high public debt levels and possible non-linearity. Several authors tried to validate Reinhart and Rogoff's (2010) findings via growth regressions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…See e.g. [Herndon, Ash, Pollin 2013;Krugman 2013]. 4 It is important to add that a critical threshold for debt level depends on an individual position of a particular country including such factors as the share of foreign debt in total debt, the average maturity of debt, the value of the assets held by general government, country's demographic structure, but also on the phase of the business cycle and the risk aversion of investors.…”
Section: Impact Of Public Debt On the Economic Growth And The Level Omentioning
confidence: 99%